Bronze and Iron Age Sites in Srem and the Stratigraphy of Gomolava - Tasić, Nikola (Balcanica - Annual of the Institute for Balkan Studies, 2005)
Systematic excavation at Gomolava conducted almost interruptedly between 1953 and 1985 provided an almost full insight into the human occupation of the southern Pannonian Plain from the Early Neolithic to the successive arrival of Celts and Romans. This fact makes it possible for many of the excavated short-lived or horizontally-stratified settlements to be defined in relation to Gomolava’s stratigraphic sequence. As a result, the paper attempts to establish a relative chronology for Bronze and Iron Age sites in the area between the Sava and Danube rivers. By way of illustration, it offers four maps suggesting synchronous developments. Thus Map 1 shows chronological parallelism between the Early Bronze Age layers and late Vučedol and Vinkovci sites (such as Pećine near Vrdnik, or Belegiš, Vojka and Batajnica) belonging to the final Eneolithic and Early Bronze, while Map 2 shows synchronisms between Gomolava IVb–c and the Vinkovci layers at the sites of Gradina on the Bosut, Gradac at Belegiš, Petrovaradin Fortress, and Asfaltna Baza on the outskirts of Zemun. The end of the Bronze Age represented by Gomolava IVb1 to IVc is shown to be synchronous with the settlements, necropolises and hoard horizons of an Ha A1 and A2 date. Finally, Early Iron Age sites are easy to fit in with the Srem sites owing to systematic excavations at Gradina on the Bosut near Šid, Kalakača near Beška and numerous hoards of bronze artefacts marking a clear boundary between the Bronze and Early Iron Ages. At Gomolava this transition is reflected in horizons Va to Vd: the earliest is represented by black channelled pottery of the Gava type, while the other three are connected with the evolution of the Bosut-Basarabi complex.